Religiosity in the Mirror of Ethnic and Gender Identity Among Russians, Tuvans, and Altaians (Based on Research Materials from Altai Krai, Republic of Tuva, and Altai Republic) - Noyanzina, Oksana E.; Maksimova, Svetlana G.; Omelchenko, Darya A. (The New Research of Tuva, 2025)
The article assesses the religiosity of men and women in relation to their ethnic and confessional identification within three South Siberian regions of Russia: Altai Krai, Altai Republic, and the Republic of Tuva. The study employs the Centrality of Religiosity Scale (CRS). The religiosity of representatives of three ethnic groups (Russians, Altaians, and Tuvans) is examined from a gender analysis perspective and through the identification of five dimensions of religiosity (intellectual, ideological, public and private religious practices, religious experience). The analysis draws upon data from an original sociological study conducted in 2024 in Altai Krai (n=519), Altai Republic (n=462), and Tuva (n=361). Distinct characteristics were identified in the manifestation of religiosity and mystical feelings among men and women. A higher level of religiosity was observed among women belonging to the dominant ethnic confessions: Orthodox Russians; Tuvans, adhering to Buddhist, Shamanistic, or syncretic beliefs; and White Faith (Ak Jang) Altaians. Compared to Russian women, Tuvan and Altaian women demonstrate greater religiosity, the significance of faith constructs, and the role of the religious sphere in both internal spiritual and external secular life. The content of religiosity components reveals not only gender-based but also ethnically conditioned differences. There is a lower prevalence of “fervent” faith among women of all ethnicities and confessions compared to men. Women’s faith is generally less overtly religious, becoming especially significant at certain points in their lives. In contrast, men’s expression of faith and attachment to it is more polarized, and men are more likely to publicly demonstrate their religiosity. Russian women are significantly less likely than Tuvan and Altaian women to be confident in the presence of a guiding hand of God or a higher power. Tuvan and Altaian women, in contrast to Russians, are much more inclined to manifest themselves in the mystical and magical spheres outside of religion.